Pore structure evolution and geological controls in lacustrine shale systems with implications for marine shale reservoir characterization - Li, Hu; Xu, Ziqiang; Gao, Xiaodan; Xie, Jiatong; Qin, Qirong; Wang, Haijun; He, Shun (Scientific reports, 2025)
Understanding pore structure evolution in lacustrine shale systems provides critical insights for marine shale reservoir characterization. This study presents an integrated petrological and petrophysical analysis of a representative lacustrine shale succession, employing low temperature nitrogen adsorption (LTNA), whole rock X-ray diffraction (XRD), and scanning electron microscopy (SEM). The study shows that (1) Clay-dominated pore systems evolve through distinct pathways compared to marine shales, with illite/smectite mixed-layer minerals generating abundant mesopores through diagenetic transformation. (2) Organic matter- dominated pores display limited connectivity due to Type III kerogen characteristics and hydrocarbon generation-induced pore occlusion, contrasting with marine shale systems dominated by Type II kerogen. (3) Comparative analysis demonstrates that lacustrine shales preserve 30–40% higher micro-mesopore volumes than their marine counterparts under similar thermal maturity conditions, attributed to enhanced clay mineral diagenesis in freshwater environments. These findings provide a new framework for understanding pore structure development in non-marine depositional systems and provide valuable analogs for marine shale reservoir evaluation, particularly in transitional marine-lacustrine basins.